Partial replacement of fish meal with leucaena leucocephala seeds meal on nile tilapia (oreochromic niloticus linnaeus 1757) fingerlings - Nurul Nabilah Abdul Rahman Adrin (2018)
This study was conducted on partial replacement of fish meal with different percentage of Leucaena luecocephala seed meal (LSM) which are Diet 1 = 0 % LSM, Diet 2 = 25 % LSM and Diet 3 = 30 % LSM on Nile tilapia (Oreochromic niloticus) fingerling. The used of L. leucocephala seed were expected to give higher nutrition value for fish dietary as well as it come from legume plant that are easily growth and cheaper than fish meal. The diet were fed to the Nile tilapia (O. niloticus) fingerlings for six weeks in order to determine their growth performance. Data were collected on fish growth, feed consumption and survival rate. Different percentage of the L. leucocephala seed meal were produced different growth rate performance. At the end of the experiment, all the treatment diet showed positive growth effect. Diet 2 containing 25 % of L. leucocpehala seed meal showing the best growth performance with the best weight gain 6.35 g/fish, specific growth rate (SGR) 0.90 %, and feed conversion ratio (FCR) that is 2.45 among other but lowest on the survival rate that is 85.56 %. Nevertheless, there is no significant difference between weight gains, SGR, FCR and survival rate from all the treatment diets.